2012
DOI: 10.1007/s10461-012-0276-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-Injection and Injection Drug Use and STI/HIV Risk in the United States: The Degree to which Sexual Risk Behaviors Versus Sex with an STI-Infected Partner Account for Infection Transmission among Drug Users

Abstract: We used the National Longitudinal Study of Adolescent Health (N=14,322) to measure associations between non-injection crack-cocaine and injection drug use and sexually transmitted infection including HIV (STI/HIV) risk among young adults in the United States and to identify factors that mediate the relationship between drug use and infection. Respondents were categorized as injection drug users, non-injection crack-cocaine users, or non-users of crack-cocaine or injection drugs. Non-injection crack-cocaine use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
80
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 32 publications
(44 reference statements)
7
80
0
2
Order By: Relevance
“…In addition, several other severe physical and mental health problems are common in crack users, rendering these a high-risk population for individual and public health. For example, numerous studies have identified crack use as an independent risk factor -whether through direct drug use-related, or indirect risk (e.g., sex-related) risk behaviors -of several chronic infectious diseases (CIDs), including HCV, HIV, Tuberculosis, and rates for these CIDs are commonly higher among crack users compared to other illicit drug users (Booth, Kwiatkowski, & Chitwood, 2000;DeBeck et al, 2009;Edlin et al, 1994;Fischer et al, 2006;Howard, Klein, Schoenbaum, & Gourevitch, 2002;Khan et al, 2013;Nyamathi et al, 2002;Tortu, Neaigus, McMahon, & Hagen, 2001). Crack users indicate disproportionately elevated rates of psychiatric problems, including depression, anxiety and personality disorders, and suicide attempts (Conway, Compton, Stinson, & Grant, 2006;Ford et al, 2009;Kessler, Chiu, Demier, & Walters, 2005;Torchalla, Strehlau, Li, & Krausz, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several other severe physical and mental health problems are common in crack users, rendering these a high-risk population for individual and public health. For example, numerous studies have identified crack use as an independent risk factor -whether through direct drug use-related, or indirect risk (e.g., sex-related) risk behaviors -of several chronic infectious diseases (CIDs), including HCV, HIV, Tuberculosis, and rates for these CIDs are commonly higher among crack users compared to other illicit drug users (Booth, Kwiatkowski, & Chitwood, 2000;DeBeck et al, 2009;Edlin et al, 1994;Fischer et al, 2006;Howard, Klein, Schoenbaum, & Gourevitch, 2002;Khan et al, 2013;Nyamathi et al, 2002;Tortu, Neaigus, McMahon, & Hagen, 2001). Crack users indicate disproportionately elevated rates of psychiatric problems, including depression, anxiety and personality disorders, and suicide attempts (Conway, Compton, Stinson, & Grant, 2006;Ford et al, 2009;Kessler, Chiu, Demier, & Walters, 2005;Torchalla, Strehlau, Li, & Krausz, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…O estado civil e a exposição a drogas apresentou significativa associação ao diagnóstico de sífilis, e o percentual (11%) de indivíduos casados que se coinfectaram pode induzir ao raciocínio equivocado de que pessoas com esse tipo de vínculo afetivo tenham menos chances de contrair IST. O consumo de álcool e drogas estão entre os principais determinantes para a transmissão de agentes infecciosos, sendo reflexo da adoção de práticas de risco, como multiplicidade de parceiros sexuais, prática de prostituição e uso incorreto ou inexistente de preservativo (26)(27) .…”
Section: Discussionunclassified
“…In addition to these welldocumented risk factors, a review of patients' charts revealed 33.1% of our study population had a history of drug abuse and 7.4% had a history of sex abuse. While the association between injection drug use, needle sharing and contraction of blood born pathogens is direct, use of non-injection drugs is associated with heightened risk for HIV contraction via risky sex behavior; those who use non-injection drugs have diminished inhibitions, are often more sexually active, involved in prostitution, have lower condom use and more commonly engage in anal sex [32]. A history of sex abuse is also substantially more common in patients with SMI, and is associated with an increase in high-risk sexual activity and further sexual assault [11,33].…”
Section: Discussionmentioning
confidence: 99%